The prevention and detection of computer fraud - Collier, P. A. (Paul A.); Dixon, R.; Marston, C L. (London : CIMA, 1990)
The study examines the involvement and atitudes of senior financial managers and internal auditors to the prevention and detection of computer fraud.
oif 18/02/15
Loan
Keywords: Fraud -- Computers; Computer crimes -- Great Britain; Social Welfare